High live birth rates after laparoscopic isthmocele repair in infertility: a systematic review and meta-analysis - Vidal, Angela; Geiger, James; Vinayahalingam, Vithusha; Pape, Janna; Gulz, Marietta; Karrer, Tanya; Mueller, Michael D.; von Wolff, Michael (Frontiers in Endocrinology, 2025)
BackgroundCesarean sections are becoming more common worldwide. One of the long-term complications of cesarean section is a cesarean scar defect or isthmocele. The presence of isthmocele is associated with infertility.ObjectivesThis systematic review and meta-analysis examined the effect of laparoscopic isthmocele repair on the reproductive outcomes of patients with and without infertility.Search strategyWe searched MEDLINE, EMBASE, and the Cochrane CENTRAL databases in April 2024.Selection criteriaThe study included cohort studies, case-control studies, and case series reporting reproductive outcomes after laparoscopic isthmocele repair among women with or without diagnosed infertility.Data collection and analysisThe meta-analysis examined rates of live birth, pregnancy, and miscarriage.Main resultsThe search identified 866 records and 17 articles were included. Clinical pregnancy rates after isthmocele resection were 62% (95% confidence interval (CI) 54-69%) in women with infertility, compared to 33% (95% CI: 16-57%) in women without infertility and 36% in women with unknown fertility status (36%, 95% CI: 21–55%). Live birth rates were 72% (95% CI: 54–85%) among those with infertility, 78% (95% CI: 46–94%) among those without infertility, and 61% (95% CI: 42–77%) with unknown fertility status. Women with and without infertility had low miscarriage rates of 10% (95% CI: 6–16%) and 7% (95% CI: 3–18%), respectively. The prevalence of co-existing endometriosis was 29% (95% CI: 22–37%). The statistical heterogeneity of the studies ranged from 0 to 86%.ConclusionsLaparoscopic isthmocele repair has demonstrated the potential to improve reproductive outcomes, specifically in cases where infertility is linked to isthmocele-related factors, such as challenges during embryo transfer or impaired implantation. However, further well-designed multicenter trials must confirm these findings and provide stronger evidence.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier (CRD42024548864).